2011
DOI: 10.1007/s10368-011-0181-4
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between homeownership and unemployment? Evidence from German regional data

Abstract: Using German regional data for 1998, 2002 and 2006, this study examines the Oswald hypothesis, the conjecture that high levels of homeownership are linked to inferior outcomes in the labor market. Applying a set of control variables, three different econometric models are specified and estimated: a cross-sectional model, a pooled data model, and a model taking into account unobserved regional heterogeneity. Once unobserved regional effects are accounted for, the findings are consistent with Oswald's hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Employment and household income are important factors (see Lerbs 2011;Giussani et al, 1992;Baffoe-Bonnie, 1998). Smith and Tesarek (1991) examined the effect of a real estate activity decrease and found that the latter leads to a decreased employment growth rate.…”
Section: Employmentmentioning
confidence: 99%
“…Employment and household income are important factors (see Lerbs 2011;Giussani et al, 1992;Baffoe-Bonnie, 1998). Smith and Tesarek (1991) examined the effect of a real estate activity decrease and found that the latter leads to a decreased employment growth rate.…”
Section: Employmentmentioning
confidence: 99%
“…A full review of the literature on the Oswald hypothesis is beyond the scope of this paper, but it is worth noting that evidence on the Oswald hypotheses is mixed. Papers supporting the Oswald hypothesis include Pehkonen (1999), Lerbs (2011), andIsebaert et al (2015). On the other hand, Flatau et al (2003), Munch et al (2006), andValletta (2013) have results that contradict the Oswald hypothesis.…”
Section: Notementioning
confidence: 99%
“…no Lerbs (2010) regi ons wi thi n Germa ny (87) 1998, 2002 a nd 2006 (3 obs erva ti ons ) Sepa ra te regres s i ons per yea r (OLS), Pa nel da ta : pool ed OLS, fi xed effects OLS.…”
Section: Oswald?unclassified
“…Studies using macroeconomic data are more often in line with Oswald (e.g. Partridge and Rickman, 1997;Pehkonen, 1997;Nickell, 1998;Nickell et al 2005;Cochrane and Poot, 2007), although various researchers obtain dissident or insignificant results (Flatau et al, 2002;Barrios Garia andHernandez, 2004, Coulson andFisher, 2009;Lerbs, 2010). Overall, it is difficult however to draw convincing conclusions from these macro studies due to their imperfect or limited econometric setup.…”
Section: Introductionmentioning
confidence: 99%